Orthopaedic surgery residency match trends during COVID-19 pandemic: a cross-sectional study. Issue 5 (20th September 2022) - Hayward, Dan; Dowdle, Travis S.; Steadman, Jesse; Froerer, Devin; Perry, Cody; Zumwalt, Mimi
Abstract : Background: Orthopaedic surgery is one of the more competitive specialties for medical students to pursue. Students often complete subinternship rotations to demonstrate skill, work ethic, and fit within a program. Away rotations were suspended during the COVID-19 pandemic. Methods: This investigation compared home and regional match rates before the pandemic to the match cycle of 2020-2021. Results: There was a statistically significant increase in students matching to their home program, and insignificant increase in regional matches. Conclusions: This increase is likely due in part to the familiarity of students to programs where they could still rotate during the pandemic. Level of Evidence: Level IV.